2015
DOI: 10.1101/gad.256628.114
|View full text |Cite
|
Sign up to set email alerts
|

Brg1 promotes both tumor-suppressive and oncogenic activities at distinct stages of pancreatic cancer formation

Abstract: Pancreatic ductal adenocarcinoma (PDA) develops predominantly through pancreatic intraepithelial neoplasia (PanIN) and intraductal papillary mucinous neoplasm (IPMN) precursor lesions. Pancreatic acinar cells are reprogrammed to a "ductal-like" state during PanIN-PDA formation. Here, we demonstrate a parallel mechanism operative in mature duct cells during which functional cells undergo "ductal retrogression" to form IPMN-PDA. We further identify critical antagonistic roles for Brahma-related gene 1 (Brg1), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
119
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 66 publications
14
119
1
5
Order By: Relevance
“…We confirmed the differential expression of various genes in these categories by qRT-PCR analysis in E1A; HRasV12;wild-type and E1A;HRasV12;Neat1 −/− MEF lines, focusing on genes such as Srgap3, Dll1, Reln, and Plxna4, which have been shown previously to display tumor suppressor activity (Sato et al 2006;Balakrishnan et al 2009;Zhang et al 2011;Castellano et al 2016). Moreover, given that deficiency in SWI/SNF complex function leads to the formation of IPMNs in mouse models for PDAC (von Figura et al 2014;Roy et al 2015), we also queried the status of chromatin remodeling gene expression in E1A;HRasV12;Neat1 −/− MEFs using the RNA-seq data. Interestingly, we found that expression of various SWI/SNF components, such as Smarca1 and Smarcc2, was reduced in Neat1-deficient cells relative to controls (Fig.…”
Section: Neat1 Deficiency Induces Global Gene Expression Profile Changessupporting
confidence: 76%
“…We confirmed the differential expression of various genes in these categories by qRT-PCR analysis in E1A; HRasV12;wild-type and E1A;HRasV12;Neat1 −/− MEF lines, focusing on genes such as Srgap3, Dll1, Reln, and Plxna4, which have been shown previously to display tumor suppressor activity (Sato et al 2006;Balakrishnan et al 2009;Zhang et al 2011;Castellano et al 2016). Moreover, given that deficiency in SWI/SNF complex function leads to the formation of IPMNs in mouse models for PDAC (von Figura et al 2014;Roy et al 2015), we also queried the status of chromatin remodeling gene expression in E1A;HRasV12;Neat1 −/− MEFs using the RNA-seq data. Interestingly, we found that expression of various SWI/SNF components, such as Smarca1 and Smarcc2, was reduced in Neat1-deficient cells relative to controls (Fig.…”
Section: Neat1 Deficiency Induces Global Gene Expression Profile Changessupporting
confidence: 76%
“…That said, the biology of these chromatin regulators and their impact on cancer progression and/or suppression are not well understood and appear to be highly context-specific. For instance, while Smarca4 deficiency promotes oncogenic Kras-driven PDAC development in GEMMs, its reconstitution in SMARCA4-null tumors provokes an EMT phenotype with dramatically enhanced tumor growth, suggesting different functions in tumor genesis versus tumor maintenance (Roy et al 2015). Thus, the optimal therapeutic prosecution of these chromatin modulator drivers will necessitate a thorough understanding of their context-dependent actions on both genetic and cell biological levels.…”
Section: Pdac Epigeneticsmentioning
confidence: 99%
“…Specifically, reconstituted SMARCA4 expression in SMARCA4-deficient human PDAC cells suppresses cell growth (Shain et al 2012), and a GEMM shows that cooperation with Smarca4 deletion and oncogenic Kras promotes IPMN development and PDAC progression with shortened overall survival compared with mice engineered with oncogenic Kras alone (von Figura et al 2014). Interestingly, Smarca4 loss leads to dedifferentiation of pancreatic ductal cells and formation of IPMNlike precursor lesions (Roy et al 2015). This observation, coupled with the multiple cells of origin for PanIN lesions (Gidekel Friedlander et al 2009;Kopp et al 2012) and the established critical role of epigenetic modifications during cellular development and lineage specification (Orkin and Hochedlinger 2011), prompts speculation that these chromatin modulators may lie at the nexus of cellular plasticity processes that provide a permissive developmental state for oncogenic KRAS-driven transformation across various cell types.…”
Section: Pdac Epigeneticsmentioning
confidence: 99%
“…The results demonstrated that like certain other genes [52,53], ANGPTL4 plays a yin-yang role depending on tumor stage; it promotes malignancy of cutaneous melanoma cells and ameliorates the malignant phenotype of brain-metastasizing cells.…”
Section: Discussionmentioning
confidence: 92%